HUBUNGAN EXPLOSIVE POWER OTOT LENGAN DAN BAHU DENGAN HASIL PUKULAN BACKHAND PERMAINAN BULU TANGKIS PADA EXTRAKULIKULER PUTRA PSBR RUMBAI PEKANBARU - Riana FitriHandayani FitriHandayani; Slamet '; Saripin ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : The result of field observation study has found problems at student psbr rumbai pekanbaru in did blow backhand and the result are not satisfactory. So that these skill develop better it need the tranning and discipline at student psbr rumbai on practice. Be sides the condition of physical also need the skiil of meet to be result maximum performance.Thetype of research research of correlation with total student psbr is 11 person. Data in this research is thecnique total sampling. Sample this research is over all number of students it that 11 person. And the instument this research is exsplosive power and blow of backhand be used two hands medicine ballblow ofbackhand.Then data processed with statistic to test normality with test liliforst at signifikan level α=0,05, proposed hypothesis is the connection explosive power of arm muscle and shoulder with the result of belting backhand trick played on badminton. And the analysis of data have result is there connect explosive power of muscle and shoulder (x) with result blow of backhand (y) at student of psbr rumbai.and the calculation is rhitung= 0,763 >rtabel= 0,632there is connect exsplosive power of arm muscle and shoulder (x) with result blow of backhand. It can be concluded that ho is rejected and ha be accepted and is shows there have connect between two variables. Key word    : exsplosive power, arm muscle and shoulder, result blow of backhand in badminton.